Diverse Stomatal Behaviors Mediating Photosynthetic Acclimation to Low Temperatures in Hordeum vulgare - Jurczyk, Barbara; Grzesiak, Maciej; Pociecha, Ewa; Wlazło, Magdalena; Rapacz, Marcin (Frontiers in Plant Science, 2019)
PPhotosynthetic acclimation to cold conditions is an important factor influencing freezing tolerance of plants. Photosynthetic enzyme activities increase as part of a photochemical mechanism underlying photosynthetic acclimation to low temperatures. Additionally, a non-photochemical mechanism may be activated to minimize photooxidative damage. The aim of this study was to test the hypothesis that differences in stomatal conductance in Hordeum vulgare plants with contrasting freezing tolerances induce various strategies for photosynthetic acclimation to cold stress. Different stomatal behaviors during the prehardening step resulted in diverse plant reactions to low-temperature stress. Plants with a relatively low freezing tolerance exhibited decreased stomatal conductance, resulting in decreased photochemical activity, faster induction of the non-photochemical mechanism, and downregulated expression of two Rubisco activase (RcaA) splicing variants. In contrast, plants with a relatively high freezing tolerance that underwent a prehardening step maintained the stomatal conductance at control level and exhibited delayed photochemical activity and RcaA expression decrease, and increased Rubisco activity, which increased net photosynthetic rate. Thus, in barley, the induction of photoinhibition avoidance (i.e., non-photochemical photoacclimation mechanism) is insufficient for an effective cold acclimation. An increase in cold-induced net photosynthetic rate due to open stomata is also necessary.